Strengthening democracy throughout the world - Hopkinson, Nicholas (HMSO LondonGB, 1994)
Examines the many preconditions necessary for a 'free and fair' election; the role of bilateral donors and inter-parliamentary associations; how election monitoring can contribute to achieving a 'free and fair' election; the need for greater international co-operation in electoral assistance, and case studies of recent elections viz. Guyana, Kenya and Nepal.